Zoo city - Beukes, Lauren (New York Brown and Company, 2016)
Zinzi has a talent for finding lost things. To save herself, she has to find the hardest thing of all - the truth. Zinzi has a Sloth on her back, a dirty 419 scam habit and a talent for finding lost things. But when a client turns up dead and the cops confiscate her last paycheck, she's forced to take on her least favourite kind of job - missing persons. Being hired by famously reclusive music producer Odi Huron to find a teenybop pop star should be her ticket out of Zoo City, the festering slum where the criminal underclass, marked by their animals, live in the shadow of the undertow. Instead, it catapults Zinzi deeper into the underbelly of a city twisted by crime and magic, where she'll be forced to confront the dark secrets of former lives - including her own. Set in a wildly re-imagined Johannesburg, it swirls refugees, crime, the music industry, African magic and the nature of sin together into a heady brew
Originally published in hardcover by Angry Robot, 2010"--Title page verso.
Keywords: Missing persons--Investigation--Fiction.